Adolf Hitler: The Role of the Leader In the Development of National Socialism - Dibben, Judy Margaret Curtis (My University, 1965)
An analysis of the part played by Hitler in German history to illustrate the important role personality can play in determining political events. Particular attention is paid to the reasons for the downfall of the Weimar Republic to see what role, if any, they played in shaping Hitler’s career; to a delineation of the kind of person who was attracted to Hitler’s banner; to Hitler’s ability to develop the N.S.D.A.P. and lead it to power; to Hitler’s position in the formation of the Third Reich and his supremacy within that regime; and to the ideology that dominated his personality.
Keywords: Political Economy